2015
DOI: 10.1002/pssa.201532316
|View full text |Cite
|
Sign up to set email alerts
|

Growth mechanisms of GaN microrods for 3D core–shell LEDs: The influence of silane flow

Abstract: The three-dimensional growth of GaN structures as a basis for the fabrication of 3D GaN core-shell LEDs has attracted substantial attention in the past few years. GaN nanorods or microrods with high aspect ratios can be grown by selective area epitaxy on a GaN buffer through a SiO x mask. It has been found earlier that silane substantially initiates vertical growth, with the exact underlying mechanisms being still unclear. Here, the influence of silane on the 3D GaN column growth was investigated by performing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 29 publications
0
49
0
Order By: Relevance
“…Since the GaN columns show no c-plane on top after and during growth, which means that c-plan grows so fast that it vanishes, and the columns end with semi-polar planes and look like a pencil; the m-planes do not grow at all so that the limiting planes are the semipolar ones during the 3D growth process. 43 Although Si was not analyzed on similar rods overgrown by an LED structure, a Si-rich layer was detected by transmission electron microscopy based energy dispersive X-ray spectroscopy as well as by Auger spectroscopy of the sidewall surface. 43 This Si-rich layer is believed to strongly influence the diffusion of growth species on the m-planes and, thus, promotes 3D growth.…”
Section: Results and Disscusionmentioning
confidence: 99%
“…Since the GaN columns show no c-plane on top after and during growth, which means that c-plan grows so fast that it vanishes, and the columns end with semi-polar planes and look like a pencil; the m-planes do not grow at all so that the limiting planes are the semipolar ones during the 3D growth process. 43 Although Si was not analyzed on similar rods overgrown by an LED structure, a Si-rich layer was detected by transmission electron microscopy based energy dispersive X-ray spectroscopy as well as by Auger spectroscopy of the sidewall surface. 43 This Si-rich layer is believed to strongly influence the diffusion of growth species on the m-planes and, thus, promotes 3D growth.…”
Section: Results and Disscusionmentioning
confidence: 99%
“…2(d)) would have similar mechanism with VLS, because the nanowires have a high aspect ratio of $100, which can not be realized by using normal SAG. [7][8][9][16][17][18]20,22,23 The underlying growth mechanism in this case would be neither pure VLS 1,2,12,13,24-27,29 nor pure SAG, 7-9,16-18,22,23 because of the factors: (1) for VLS, metal droplet can normally be observed at the tip of nanowires, but in our case there is no droplet at the tip of nanowires (Fig. 2(d)) or needles (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2 achieved nanowire arrays via VLS at 780 C. Tian et al 36 prepared micro-pyramids via SAG at a high temperature about 1080 C. Bae et al 37 investigated the morphologies of micro-pyramids, and they found that micropyramids with smooth sidewalls can only be grown at the temperature higher than 900 C. Rozhavskaya et al 3 reported the growth of micro-rod arrays under 1040 C. Thus, growth temperature of these micro-structures prepared via SAG (950-1175 C) [7][8][9][16][17][18]22,23 is much higher than that of nanowires prepared via VLS (760-850 C). 1,2,12,13,[24][25][26][27]29 Thus, it is still a challenge to simultaneous growth of all these nanostructures (including nanowires and micro-rods) under a favorable condition.…”
Section: 11mentioning
confidence: 99%
“…The template is heated up in the reactor under N 2 carrier gas before a short growth step under a high V/III ratio of 1000 and under H 2 carrier gas is performed to start the growth of the GaN cores in the hole openings. Subsequently, the 3D-growth step of the microrods is carried out under a low V/III ratio of 77 and a SiH 4 flow of 37 nmol/min for an n-type doping and an increased vertical growth rate [44,45]. The temperature during this 20-min-long step is held at 1060°C.…”
Section: Sample Growth and Focused-ion-beam Sample Preparationmentioning
confidence: 99%